Nesessary and sufficient conditions for occurrence of ethnical conflicts in Ukraine - Orlov М. М.; Halep, V. V.; Antonets, V. V. (Honor and Law, 2019)
Overlooked the conditions for occurrence of ethnical conflicts in Ukraine based on long-time social and politics instability in the state and features of certain regions with high density population of minorities. Outlined possible outcomes of ethnical conflicts. Defined place and role of interior troops in case of law enforcement units operating in the area. Predicted the general service and combat tasks of Interior Troops.